Machine learning and validation reveal that immune-related genes in systemic lupus erythematosus regulate apoptosis and cycle progression in diffuse large B-cell lymphoma - Ruan, Shengting; Wang, Shan; Jiang, Ying (Frontiers in Medicine, 2025)
IntroductionSystemic lupus erythematosus (SLE) and diffuse large B-cell lymphoma (DLBCL) are both characterized by immune dysregulation. SLE has been reported as a risk factor for DLBCL. However, the common molecular and pathophysiological mechanisms of these two diseases are not fully understood.MethodsWe first used machine learning to screen for key immune-related genes (IRGs) that were common in SLE patients and DLBCL patients. These key IRGs may be key factors promoting the progression of DLBCL and were analyzed for their potential cross-talk mechanisms in the immune microenvironment of SLE and DLBCL. Finally, we verified the potential functions of IRGs in the development of DLBCL through cell experiments.ResultsA univariate analysis and machine learning confirmed that the CD247 molecule (CD247) was a common key gene in SLE and DLBCL. Meanwhile, the immune analysis results indicate that high expression of CD247 may enhance T-cell mediated anti-tumor immunity by regulating the immune infiltration of CD8 + T cells. Cell experiments have shown that overexpression of CD247 can significantly inhibit cell cycle progression and promote apoptosis in DLBCL cells.DiscussionIn short, this study determined that the CD247 gene may be a key gene in SLE-induced DLBCL, as it participates in the immune response and can induce DLBCL apoptosis and cell cycle changes.